Hydrocarbon Potential and Organic Matter–Inferred Depositional Conditions of the Shiranish Formation in Diana Subdistrict, Northeastern Iraq: Evidence from FTIR Spectroscopy and Palynological Analysis (Iraqi National Journal of Earth Science (INJES), 2026)
The Shiranish Formation, which is known for its dual function as a source and reservoir rock, is a crucial geological unit for hydrocarbon exploration in northern Iraq. In this work, the kerogen types and organic matter properties of the Shiranish Formation in the Diana Sub-district of the Kurdistan Region of Iraq are examined. Using a combination of FTIR Spectroscopy and visual kerogen microscopy, samples were gathered and examined. The results show that all samples include amorphous organic matter (AOM) predominating, with varying contributions from phytoclasts and palynomorphs, according to palynofacies analysis. This suggests a marine anoxic to dysoxic depositional environment. Functional groups linked to both aromatic and aliphatic chains are identified by FTIR spectra, suggesting the existence of heterogeneous organic matter that is prone to both gas and oil. However, the organic matter is consistently classified as Type II/III with early to peak oil window maturity using the Rock-Eval pyrolysis criteria (TOC, HI, and Tmax). In addition, well-preserved marine palynomorphs like Arecipites microfoveolatus and Thermal Alteration Index (TAI) values of 2 to 2.5 suggest early thermal maturity and deposition in suboxic to anoxic marine environments. These findings are further supported by kerogen microscopy, which shows a dominant quantity of liptinite and organized AOM. According to the integrated data, the Shiranish Formation, which was formed in the research region under mostly anoxic marine conditions, is a possible source rock with favorable conditions for hydrocarbon formation.
Keywords: Cretaceous, Shiranish, kerogen, Infrared spectroscopy, Iraq.